Building an Index System for Evaluating the Motor Health of Preschool-aged Children from the Perspective of Disciplinary Intersections: A Delphi Study - Dongxu Du; Chairat Choosakul (Physical Education Theory and Methodology)
Background. Sports health and the future of preschool children are urgent problems. However, a comprehensive and scientific evaluation index system (EIS) for assessing their sports health is lacking.